Synthesis and properties of 3-(ethylthio)-9-methyl-6-(alkylthio) pyrazolo[1,5-d][1,2,4]triazolo[3,4-f][1,2,4]triazines - Fedotov, S. O.; Hotsulia, A. S.; Федотов, Сергій Олегович; Гоцуля, Андрій Сергійович (Запорізький державний медичний університет, 2022)
The aim of the work was to identify optimal conditions for the production of 3-(ethylthio)-9-methyl-6-(alkylthio)pyrazolo[1,5-d][1,2,4] triazolo[3,4-f][1,2,4]triazines and to study the properties of the target reaction products. Materials and methods. The chemical part of the work involved the step-by-step creation of target reaction products in the form of 3-(ethylthio)-9-methyl-6-(alkylthio)pyrazolo[1,5-d][1,2,4]triazolo[3,4-f][1,2,4]triazines. The first stage was aimed at conducting the interaction of diethyloxalate with acetone with the participation of sodium methylate in a methanol medium. Ethyl-2,4-dioxopentanoate was used in the conversion process to 3-methylpyrazole-5-carbohydrazide with the participation of hydrazine hydrate. Further modification of the molecule consisted of the gradual formation of the structure of 4-amino-5-(3-methylpyrazol-5-yl)-1,2,4-triazole-3-thiol. The next step involved the synthesis of 3-ethylthio-5-(3-methylpyrazol-5-yl)-1,2,4-triazole-4-amine. Further conversion included the production of potassium 3-ethylthio-9-methylpyrazolo[1,5-d][1,2,4]triazolo[3,4-f][1,2,4]triazine-6-thiolate and its S-alkyl derivatives along the triazine fragment. Cyclooxygenase-2, lanosterol-14α-demethylase and receptor tyrosine kinase were selected as model enzymes for docking, the crystal structure of which was loaded from the Protein Data Bank. Мета роботи – визначення оптимальних умов отримання 3-(етилтіо)-9-метил-6-(алкілтіо)піразоло[1,5-d][1,2,4]тріазоло[3,4-f][1,2,4] тріазинів і дослідити властивості цільових продуктів реакції. Матеріали та методи. Хімічна частина роботи передбачала поетапне створення цільових продуктів реакції – 3-(етилтіо)-9-метил-6-(алкілтіо)піразоло[1,5-d][1,2,4]тріазоло[3,4-f][1,2,4]тріазинів. Перший етап мав на меті проведення взаємодії діетилоксалату з ацетоном за участю натрій метилату в середовищі метанолу. Одержаний етил-2,4-діоксопентаноат на наступному етапі застосували у процесі перетворення у 3-метилпіразол-5-карбогідразид за участю гідразин гідрату. Надалі модифікація молекули полягала в поетапному формуванні структури 4-аміно-5-(3-метилпіразол-5-іл)-1,2,4-тріазол-3-тіолу. Наступний крок передбачав синтез 3-етил- тіо-5-(3-метилпіразол-5-іл)-1,2,4-тріазол-4-аміну. Дальше перетворення – одержання калій 3-етилтіо-9-метилпіразоло[1,5-d][1,2,4] тріазоло[3,4-f][1,2,4]тріазино-6-тіолату та його S-алкілпохідних за тріазиновим фрагментом. Як модельні ферменти для докінгу обрали циклооксигеназу-2, ланостерол-14α-деметилазу та рецепторну тирозинкіназу, кристалічну структуру яких завантажили з Protein Data Bank.
Синтез та властивості 3-(етилтіо)-9-метил-6-(алкілтіо)піразоло[1,5-d][1,2,4]тріазоло-[3,4-f][1,2,4]тріазинів
Fedotov S. O. - ORCID ID: 0000-0002-0421-5303; Hotsulia A. S. - ORCID ID: 0000-0001-9696-221X.
Keywords: 1,2,4-triazole; pyrazole; physico-chemical properties; molecular docking; 1,2,4-тріазол; піразол; фізико-хімічні властивості; молекулярний докінг